PERAN PENDIDIKAN ORANG TUA TERHADAP KENAKALAN REMAJA - Ria Lavina Khansa; Edy Soesanto (CV. ADIBA AISHA AMIRA, 2024)
According to Kartono (1992) juvenile delinquency is an abbreviation of juvenile crime. Adolescence is a time when someone searches for their identity and tries to determine who they really are. Adolescents need understanding and help from people they love and are close to, especially parents or family, during their difficult development process and confusing times. (1Syaibani.R 2019) This research aims to determine the influence of the role of parental education on delinquency. teenagers in Central Kaliabang, Kavling Rajawali, North Bekasi. The methods used in this research are quantitative and qualitative. The population of this research was 15 teenagers from Central Kaliabang, North Bekasi, using a purposive sampling technique with a sample of 15 people. The data collection technique uses a questionnaire. The questionnaire is used to reveal the variable influence of the role of parental education on juvenile delinquency in the form of a closed questionnaire statement. The research hypothesis test is simple linear regression. The results of this research show that the role of parental education influences juvenile delinquency. The variable role of parental education contributed 68% to changes in the juvenile delinquency variable, while the remaining 32% was influenced by other factors. From the results of calculations carried out by the researcher, the calculation obtained (3.256) is greater than the table (0.267) with a significance level of (0.04). So, H0 is rejected and Ha is accepted